HUBUNGAN PENGETAHUAN IBU NIFAS TENTANG PERAWATAN PAYUDARA DENGAN KELANCARAN PENGELUARAN ASI DI PUSKESMAS KOTA KABUPATEN BANTAENG - Suhartini, Suhartini; Yuliandini, Astri; Ani, Ani (STIKES Pasapua Ambon, 2023)
Introduction : Breast care during breastfeeding aims to keep the breasts always clean and easy for babies to suck. After each feeding, the breasts are immediately cleaned of splattered milk so as not to become a medium for bacteria to develop. For this reason, breast care prevents infections in the breast such as mastitis (mammary infection). Method: The research was conducted in November 2022 at the Bantaeng Regency City Health Center in 2022. This type of research is the Cross Sectional Study method. The population in this study is all postpartum mothers who are at the Bantaeng Regency City Health Center in 2022. The sample in this study was postpartum mothers who were at the Bantaeng Regency City Health Center in 2022 as many as 30 people using Purposive Sampling techniques. Results: The results showed that of the 30 people sampled, 20 people were well informed about breast care (66.7%) and 10 were less knowledgeable (33.3%). The results showed that of the 30 people used as samples, 19 people experienced smooth breastfeeding expenditure (63.3%) and 11 people (36.7%) who were not smooth. The results showed that there was a relationship between postpartum mothers' knowledge about breast care and smooth milk dispensing. Conclusion : It is expected for mothers to understand the techniques and how to do so that mothers can do according to their stages